Focus on the glycerophosphocholine pathway in choline phospholipid metabolism of cancer. (11th June 2019) - Sonkar, Kanchan; Ayyappan, Vinay; Tressler, Caitlin M.; Adelaja, Oluwatobi; Cai, Ruoqing; Cheng, Menglin; Glunde, Kristine
Abstract : Activated choline metabolism is a hallmark of carcinogenesis and tumor progression, which leads to elevated levels of phosphocholine and glycerophosphocholine in all types of cancer tested so far. Magnetic resonance spectroscopy applications have played a key role in detecting these elevated choline phospholipid metabolites. To date, the majority of cancer‐related studies have focused on phosphocholine and the Kennedy pathway, which constitutes the biosynthesis pathway for membrane phosphatidylcholine. Fewer and more recent studies have reported on the importance of glycerophosphocholine in cancer. In this review article, we summarize the recent literature on glycerophosphocholine metabolism with respect to its cancer biology and its detection by magnetic resonance spectroscopy applications. Abstract : Aberrant choline metabolism is a hallmark of oncogenesis and cancer progression, characterized by increased phosphocholine, glycerophosphocholine and total choline‐containing compounds. These oncometabolites can be detected with MRS techniques in preclinical studies and clinical settings. Detection of glycerophosphocholine by MRS can be used for diagnosis, prognosis and treatment response monitoring. Until recently, most studies have focused on the elevated phosphocholine levels in cancer, while glycerophosphocholine has remained a poorly understood oncometabolite. In this review, we summarize the recent literature on glycerophosphocholine metabolism and biology in cancer and its detection using MRS techniques.